Implementation of Case Base Reasoning Method to Detect Hard Drive Damage - Nanang, Nanang Feberianto; Pawan, Elvis; Hasan, Patmawati (International Journal of Computer and Information System (IJCIS), 2023)
Daily life includes the use of computers as electronic devices that are common in offices, libraries, schools, and shopping malls. However, users often face problems when the computer's hard drive encounters problems. As a non-formal educational institution that offers computer courses and training, Yayasan Sentra Anugrah Mandiri also experienced problems with hard drives of various brands and capacities. The technician checks and fixes the problem manually. Three people are usually responsible for monitoring twenty computers. If there is a problem, it is then reported to the administrator responsible for organizing the repair process. In this study, a website-based expert system is proposed that uses a similar approach to overcome these problems and improve the efficiency of handling hard drive problems. Retrieve, Reuse, Revise, and Revise are the four steps in the Case Base Reasoning (CBR) method.